Women’s Studies at IDELA: Memories of a Lifetime - Prada-Ortiz, Grace (2026)
This essay offers an intimate perspective, albeit historical and reflective, as a reconstruction of the emergence and consolidation of women’s studies at the Institute of Latin American Studies (IDELA) of the National University, based on the direct experience of one of its protagonists. The text shares with us the memory of an academic process that was born from intuitive, solidaritydriven, and voluntary initiatives before becoming formalized as a systematic field of study within the institution. Through situated narratives—ranging from work with Indigenous communities and women’s cooperatives to formative experiences with incarcerated women—the author shows how teaching, research, and outreach were articulated early on to introduce a critical perspective on gender inequality in Latin America as a fundamental component of discussions within Latin American studies and intellectual thought.